2012
DOI: 10.1007/s00415-011-6372-7
|View full text |Cite
|
Sign up to set email alerts
|

Is there delayed gastric emptying in patients with multiple system atrophy? An analysis using the 13C-acetate breath test

Abstract: Autonomic failure is one of the criteria according to the second consensus statement for the diagnosis of multiple system atrophy (MSA). Gastrointestinal symptoms are frequent complaints in patients with MSA and may be associated with reduced gastrointestinal motility due to autonomic nervous system dysfunction. However, there are few reports on gastric emptying in patients with MSA. We investigated gastric emptying in 25 patients with MSA, 20 patients with sporadic adult-onset ataxia of unknown etiology (SAOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Delayed GE is one of the autonomic failures and may be a clinical marker of MSA. [68] Symptoms relating to disturbed gastric motility in MSA are uncommon, although some patients have gastric fullness postmeal that may be troublesome. Drugs such as anticholinergic and dopaminergic agents are often used to treat motor disorder and may impair motility.…”
Section: Multiple System Atrophymentioning
confidence: 99%
“…Delayed GE is one of the autonomic failures and may be a clinical marker of MSA. [68] Symptoms relating to disturbed gastric motility in MSA are uncommon, although some patients have gastric fullness postmeal that may be troublesome. Drugs such as anticholinergic and dopaminergic agents are often used to treat motor disorder and may impair motility.…”
Section: Multiple System Atrophymentioning
confidence: 99%
“…The roles of the vagal system and the ENS in control of gastric emptying have been outlined and as both are early sites of alpha‐synuclein deposition, it is postulated that resultant neural damage and dysfunction contributes to impaired gastric motility. Indirect evidence supporting the hypothesis that abnormal alpha‐synuclein accumulation underlies impaired gastric motility in PD comes from studies demonstrating delayed gastric emptying in multiple system atrophy, another synucleinopathy . To the best of our knowledge, no evaluations of gastric emptying in the context of dementia with Lewy bodies have been published.…”
Section: Delayed Gastric Emptying In Pdmentioning
confidence: 99%
“…Previous studies have shown that patients with MSA frequently exhibit delayed gastric emptying [1] and slow colonic transit [2]. Accumulating evidence suggests that active ghrelin facilitates motility of the gastric antrum [4,5] and colorectum [21], and unacylated ghrelin may SCOPA-AUT gastrointestinal score Active ghrelin ratio (%) Fig.…”
Section: Discussionmentioning
confidence: 93%